Strategy for improving learning quality assessed from teachers performance in senior high - Malda Redy; Edi Harapan; Rohana Rohana (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
This study aims to identify and describe strategies for improving the quality of learning in terms of teacher performance at the State Senior High School 3 of Sekayu, the obstacles faced and the results achieved. The research data collection techniques: 1) interview, 2) observation, 3) documentation. The research data analysis technique refers to qualitative research using 3 stages: 1) the processing data, 2) the reducing data, 3) the analyzing data. The results of this study: (1) the teachers creates innovative, effective, and fun learned by using infocus and utilizing hotspot facilities. In delivering learning materials, teachers use digital literacy as a supporting means to align the learning material delivered; (2) Constraints faced by potential, intelligence, and interest in accordance with the level of development and ability of students have not been achieved than expected, where the potential, intelligence and interest of students at the State Senior High School 3 of Sekayu are different; (3) The results achieved from strategies in improving the quality of learning in terms of teacher performance at the State Senior High School 3 of Sekayu, the fulfillment of the implementation of the delivered learning, where the learning process is innovative, active, and fun in accordance with the objectives of curriculum development in 2013 which is designed which is divided into 2 ( two), namely the implementation of learned which refers to the work program for a year (prota) and the implementation of learned which refers to the work program during the semester (prosem).